Roleof Knowledge Flow in Enhancing the Dimensions of Empowerment Administrative: An Exploratory Study ofthe Opinions of Directors atthe Royal Colors Printing & Packaging in Sulaymaniyah - . منال عبد الجبار السماك; ايمان علي احمد الحيالي (Iraqi Journal for Administrative Sciences, 2024)
This research sought within its theoretical & field framework to study the implications of the knowledge flow towards the dimensions of administrative empowerment, starting from hypotheses linking the study variables of cognitive flow & administrative empowerment to achieve a tangible contribution in knowledge management & administrative empowerment to reach a work environment , By establishing the potential vision of the evolutionary approaches to the flow of knowledge & the dimension of administrative empowerment through an exploratory study of the opinions of managers at Royal Colors Printing & Packaging Company in Sulaymaniyah to represent the sample of the research, The questionnaire to collect data & information to determine the relationships between the variables of the research in order to diagnose the most influential dimension by relying on the ready software SPSS, In order to achieve this, a default scheme was prepared including search variables, as well as the formulation of a number of basic hypotheses & sub-hypotheses, which were tested through a number of statistical methods, & the limited studies that dealt with the relationship between these variables in the Iraqi environment. In an attempt to study the relationship & influence between them. Within the framework of the research was formulated the main question as follows: How can the flow of knowledge reflect a clear reflection in the dimensions of administrative empowerment in the company investigated? The results of the study were divided into 40 categories for the purpose of analysis & finding the relationship between the two variables. The research reached a number of conclusions, the most prominent of which was: A significant correlation between the cognitive flow & the dimensions of administrative empowerment was achieved. A number of recommendations have been made in line with those conclusions.